SCS 6th Annual Meeting-EEVFA-11th International Congress of Biochemistry and Physiology of Exercise, Athens, Greece, 2023 - Pedro E. Alcaraz; Elena Marín-Cascales; Anthony J. Blazevich; Tomás T. Freitas; Olyvia Donti; Konstantinos Spyrou; Gregory C. Bogdanis (MDPI AG, 2024)
On behalf of the Strength and Conditioning Society (SCS) and the Hellenic Society of Biochemistry and Exercise Physiology (EEVFA), we are pleased to present the abstracts of the SCS 6th Annual Meeting and EEVFA-11th International Congress of Biochemistry and Physiology of Exercise. The event was held at the Hellenic Olympic Committee headquarters in Athens, Greece, on 19-22 October 2023, and comprised several invited sessions from international and national speakers on a variety of topics related to biochemistry and exercise physiology, strength and conditioning practices and their application to health, injury prevention and sports performance. These included strength training in high-performance sports, sport science and training-competition load management in elite environments, biochemistry and exercise physiology and prescription, nutrition and biomechanics, among others. The conference also included different practical workshops conducted by renowned academics and practitioners on eccentric training, change of direction ability and strength and power training in professional team-sports, and ergospirometry and exercise prescription in specific populations. Finally, the event disseminated up-to-date strength and conditioning research by providing practitioners and researchers with the opportunity to present their most recent findings. In this regard, all abstracts of the communications presented at the SCS 6th Annual Meeting-EEVFA-11th International Congress of Biochemistry and Physiology of Exercise can be found in this Conference Report.